Authoritarianism and Tolerance to Uncertainty Among Students of Pedagogical Universities in Russia - Zinoveva M.E.M; Enikolopov S.N (Moscow State University of Psychology and Education, 2021)
The work is aimed at studying the current level of authoritarianism and intolerance to uncertainty among students of pedagogical universities in Russia. The main purpose of the work is to study the relationship between right-wing authoritarianism and tolerance for uncertainty among students of pedagogical universities, while the main assumption of the study is the presence of this relationship, which varies depending on the year of study, specialization and geographical location. The article presents the materials of a correlation study obtained on a sample of students of twenty-one pedagogical universities in Russia. The study (N=870) involved respondents aged 16 to 34 years (M=19,92; SD=2,04), of which 90% were female. The study was conducted in an Internet format. The authors used the B. Altmeyer's "Right-wing Authoritarianism Scale" in russian edition by N.A. Diakonova and the "New Questionnaire of tolerance-intolerance to Uncertainty" by T.V. Kornilova. The results demonstrate a significant increase in the level of authoritarianism from the first to the last year of study, and an average statistical correlation between authoritarianism and intolerance to uncertainty.